2005
DOI: 10.1136/ard.2004.029033
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atherosclerosis in patients with Wegener's granulomatosis

Abstract: Background: Several autoimmune disorders are complicated by excess cardiovascular disease. In addition to traditional risk factors, non-traditional risk factors such as endothelial activation and excessive vascular remodelling might be determinants of the progression of atherosclerosis in patients with an autoimmune disease. Objective: To evaluate whether patients with Wegener's granulomatosis (WG) have an increased prevalence of atherosclerosis and to determine predisposing factors. Methods: 29 WG patients (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 39 publications
1
89
2
5
Order By: Relevance
“…The presence of anti-SSA/Ro antibodies and dyslipoproteinemia with low levels and dysfunction of HDL is related to AT in Sjögren's syndrome 26 . The endothelial dysfunction seen in primary vasculitis is very close to the dysfunction in atherosclerosis and this aside, dyslipoproteinemia, activation of macrophages and ANCA antibodies also play a major role 27 . This study has shown the very high prevalence of common atherosclerotic risk factors such as smoking, obesity, hypertension, diet, diabetes and sedentary life style in the studied group of lupus patients, confirming findings of other authors describing higher rates in SLE than in a general aged matched population.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anti-SSA/Ro antibodies and dyslipoproteinemia with low levels and dysfunction of HDL is related to AT in Sjögren's syndrome 26 . The endothelial dysfunction seen in primary vasculitis is very close to the dysfunction in atherosclerosis and this aside, dyslipoproteinemia, activation of macrophages and ANCA antibodies also play a major role 27 . This study has shown the very high prevalence of common atherosclerotic risk factors such as smoking, obesity, hypertension, diet, diabetes and sedentary life style in the studied group of lupus patients, confirming findings of other authors describing higher rates in SLE than in a general aged matched population.…”
Section: Discussionmentioning
confidence: 99%
“…Zaenker et al [49] and de Leeuw et al [51] found increased IMT values in patients with ANCA-associated vasculitis compared with healthy controls, whereas no increase was observed in two other studies [52] (M. C. Slot and J. W. Cohen Tervaert, unpublished observation). Other markers for atherosclerosis have also been studied in patients with ANCA-associated vasculitis.…”
Section: Occurrence Of Accelerated Atherosclerosis In Vasculitismentioning
confidence: 93%
“…For example, endothelium-dependent vasodilatation of brachial arteries is impaired in patients having WG, a PSV typically involving small vessels. 76 A recent study by de Leeuw et al 77 provides the first direct evidence for enhanced atherosclerosis in PSV. In this study, common carotid artery IMT was compared between 29 patients having inactive WG and 26 control subjects.…”
Section: Apsmentioning
confidence: 97%